Społeczno-ekonomiczna sytuacja osób długotrwale bezrobotnych (na podstawie badania reprezentacyjnego) - Banaszkiewicz, Dorota (Socio-economic situation of the long-term unemployed, 2006)
Since the beginning of the 90’s the problem of employment and unemployment has been acknowledged as the most important social matter and it has been treated as a serious challenge for the Polish economy. This subject has inspired the interest of many scientists, like economists, sociologists, psychologists, who are aspiring to describe and analyze it in detail. As everybody knows the most dangerous kind of unemployment for the country’s economy as well as for the unemployed and the social groups touched by this problem is the long-term unemployment (it means staying without a job more then twelve months). The main aim of my dissertation was analyzing the causes and estimating the consequences of the long-term unemployment in material and non-material sphere for persons being without job, their families and all the local community. Achievement of this aim depended on planning and executing the empirical research into social and economic situation of people staying in long-term unemployment, registered with Gdańsk Office of Employment. The situation in the local labour market in Gdańsk is the same like in the whole country. The most important determinants of long-term unemployment are: age, education, sex and the work period. The research and statistical analysis let to estimate these features of unemployed, which are favourable for long-term staying without work. The analysis let estimate the material and non-material situation of the unemployed and their families. It seems that the results obtained in this research make it possible to identify the unemployed faster and to contribute to more effective preventive action of long-term staying without work.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1142, s. 174-186